Formas de la vida espiritual en el Oracional de Alfonso de Cartagena = Forms of spiritual life in Alfonso de Cartagena’s Oracional - Valero Moreno, Juan Miguel ca. 21. Jh. (Hispania sacra, 2020)
In this article are analyzed the characteristics of the textual and editorial tradition of the Oracional (ca. 1454). This treatise, composed by Alfonso de Cartagena, Bishop of Burgos, at the request of the nobleman Fernán Pérez de Guzmán, exposes the meaning and forms of Christian prayer. The transmission and reception of the Oracional seems limited to the second half of the 15th century and to the Castilian context. However, his spiritual imprint is decisive. The meaning of the title of the book, its origin and its place among other works of Cartagena is also studied. The Oracional assumes the schema of the scholastic quaestio, but adapts its format to an open doctrinal exposition, assimilated in part by another discursive system such as that of the epistle. The book of Cartagena, perfectly anchored in orthodoxy, is a forerunner of the devotio moderna, in which external and personal spirituality can coexist in the social frame of reference of the Castilian nobility, which shows a model of Christian republic. In this model, women and the institution of marriage play an important role.